STRATEGI AKSELERASI PENURUNAN STUNTING WILAYAH PESISIR KABUPATEN PEKALONGAN - Nur Susanti; Ardiana Priharwanti; Remilda Armika Vianti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2022)
Stunting is a chronic nutritional problem caused by lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or shorter than the standard age. The incidence of stunting in Indonesia is ranked fifth in the world, where 38 percent of the total number of children under five are stunted. The number of stunting rates in Pekalongan Regency is still quite high, recorded in 2020 from 10.316 children under five who were weighed, as many as 1.631 toddlers or 15.81 percent, although this was better than 2019, which recorded 21.43 percent of toddlers suffering from stunting. Stunting. The research objectives are to identify stunting problems in coastal areas, identify efforts and health programs that have been carried out related to the SUN (Scaling up Nutrition) program, and analyse the SWOT efforts and health programs that have been carried out as an effort to handle stunting reduction acceleration. The research design used by the writer was exploratory research with a qualitative approach supported by statistical data by triangulation of sources through in-depth interviews with key informants, and accompanying informants to seek apperceptions of various sources. The research instrument used guidance interviewing. The location of this research was in Jeruk Sari, Tegal Dowo and Karang Jompo villages. The results of the research on Handling Stunting through the SUN (Scaling up Nutrition) program in the three research areas (Jeruk Sari Village, Tegal Dowo Village and Karang Jompo Village) have been carried out quite well. Several SUN programs were carried out in the form of giving PMT, measuring toddlers, giving PMT to high-risk mothers and also Posyandu activities and mother's classes. Based on the results of in-depth interviews with triangulated informants, it was stated that the implementation of the program was more of a specific nutrition intervention. Sanitation improvements due to the tidal wave are still getting attention considering the condition of the third region being in an area affected by the tidal wave throughout the year. Culture and public trust are also considered as obstacles in accelerating stunting handling programs. The writer concludes that the SUN program that has been carried out in the three research areas is still in the form of specific nutrition interventions, namely interventions in the form of giving PMT to toddlers and pregnant women with rest and measuring toddlers. Sensitive nutrition interventions are still not optimally carried out. It is necessary to increase good cooperation between other cross-sectors so that the acceleration of stunting handling can be carried out.